Research progress on discharge readiness service practices for patients undergoing endometrial cancer surgery - Chen, Xia; Tang, Peijuan; Ma, Chunjing; Su, Mei; Sun, Jiaxin; Chang, Wenzhong; Li, Yaru; Cui, Yajuan; Wang, Yanting; Hu, Yuchong; Wang, Jia; Wei, Yinyi (Frontiers in Oncology, 2026)
ObjectiveThis narrative review aims to synthesize and evaluate existing evidence and practices regarding discharge readiness services for patients undergoing endometrial cancer (EC) surgery, with the goal of providing a reference for clinical practice and future research.BackgroundThe incidence of EC is rising globally. With the widespread adoption of enhanced recovery after surgery (ERAS) protocols and minimally invasive techniques, hospital stays are shortening, making effective discharge planning crucial for ensuring a safe transition to home and preventing readmissions.MethodsAs a narrative review, this article involved a comprehensive but non-systematic examination of literature from PubMed, Web of Science, CNKI, and Wanfang databases, focusing on key components of discharge readiness. These components include assessment tools, service content development, implementation processes, and outcome evaluation. The synthesis prioritized recent evidence and internationally recognized guidelines.ResultsThe review identifies that while generic discharge assessment tools are valuable, they require adaptation to address the specific needs of EC patients (e.g., lymphedema risk, sexual health). Effective service implementation relies on a systematic interdisciplinary collaboration model and nurse-led, personalized education (e.g., using the teach-back method). The integration of digital health platforms shows promise for supporting post-discharge care. Outcome evaluation should encompass both clinical indicators (e.g., 30-day readmission rates) and patient-reported outcomes (e.g., using the Health Education Impact Questionnaire). Current challenges include a lack of standardized pathways and fragmented community resources.ConclusionDischarge readiness is a critical determinant of recovery quality for EC surgical patients. This review consolidates core components and processes into a practical framework, highlighting the need for multidisciplinary collaboration, patient-centered education, and technology integration. Future efforts should focus on developing standardized, culturally adapted pathways and conducting robust comparative effectiveness research to establish high-quality, evidence-based service systems.Relevance to clinical practiceThis study focuses on the development of core components and processes for systematic discharge readiness services for postoperative endometrial cancer patients, as well as the identification of practice challenges. The findings advocate for the clinical adoption of standardized frameworks and the enhancement of implementation capacity to optimize discharge transitions, patient recovery, and continuity of care.